PENERAPAN LAPORAN KEUANGAN BERBASIS EXCEL UNTUK PENENTUAN MODAL KERJA DAN PERHITUNGAN PPH FINAL 0,5% PADA UNIT BISNIS POLJAM INOBI - Utami Solikah (Journal of Applied Accounting And Business, 2026)
Financial reports are an important component in business management bacause they function as a tool to record, measure, and present information related to the financial position and peformance of a business entity. However, many Business Unit actors still do not have structured financial records and adequate tax understanding. This study aims to implement a Microsoft Excel-based financial reporting system at the Poljam Inobi Business Unit, as well as to simulate the determination of working capital and the calculation of 0,5% Final Income Tax (PPh) in accordance with Government Regulation Number 23 of 2018. The research method uses a descriptive qualitative approach through observation, interviews, data collection, and documentation. The research results show that before implementing Excel, Poljam Inobi’s financial records were still rudimentary and did not produce complete financial reports in accordance with SAK EMKM, making it difficult for managers to obtain accurate financial information. After implementing an Excel-based system, finacial reports can be structured, including a general journal, general ledger, profit and loss statement, statement of finacial position, and working capital analysis. Furthermore, Excel simplifies the calculation of 0,5% Final Income Tax based on total recorded gross turnover. Therefore, implementing Excel-based financial reports improves recording accuracy, supports decision-making, and facilitates the fulfillment of tax obligations simply, efficiently, and in accordance with applicable regulations